Effects of Verbal and Tactile Cues on Gluteal Force Production and Broad Jump Distance - BJ Lehecka; Terra Daniels; Bryson Koester; Wyatt Kropp; Matthew Reeves; Ryan Waterson (International Journal of Sports Physical Therapy)
# Background